Processes of Secession and Irredentism in Bosnia and Herzegovina: History, Status, Prospects - Andrey V. Shabaga; Sara Kojovic (RUDN Journal of World History)
The purpose of the study is to analyze political processes in Bosnia and Herzegovina against the background of deep ethnic and religious contradictions. In this regard, the problem of secession and irredentism in Bosnia and Herzegovina is examined, considered in a broad historical context. The phenomenon of Bosnia and Herzegovina is shown as a result of the influence of liberal ideas, which largely stimulated the disintegration of Yugoslavia. The fierce military conflicts generated by this disintegration led to secessionist-irredentist projects on the part of the Serbian and, partly, Croatian population and Bosniak attempts to reincarnate the previous (Yugoslav) concept based on the primacy of citizenship over other forms of identity. In this regard, the options for a possible state structure are examined: unitarism (which the Bosniaks advocate) or confederation (the position of the Serbian population), in which many see the first step towards secession with the possibility of subsequent entry into a neighboring state. Croatian representatives prefer either a unitary or a confederative theory of state structure depending on the status of the Croatian ethnic group in one or another model. The analysis of the problem under study is based on the theory of the multipolar world by E.M. Primakov, which makes it possible to consider the place of Bosnia and Herzegovina both in the global dimension and on a regional scale. The study also uses the methodology of M. Weber, according to which interethnic contradictions are predetermined by the incommensurability of values, in some cases turning into the reduction of religious dogmas into social norms. The conclusion is that, due to a number of political, religious and cultural reasons considered, secessionism and irredentism are more pronounced among the Balkan peoples than among other peoples. Europe. At present, these processes are far from complete in Bosnia and Herzegovina, and even possible entry into other confederative associations, such as the EU, will not be a reliable guarantee of their cessation.